Experimental investigation of the phase equilibria, phase stability, and defect structure in the Cr–Zr system by using DSC, XRD, and SEM. (November 2022) - Samanta, Biswajit; P., Anand Kumar
Abstract: The solid-state phase transformations, phase stability, and defect structure in the Cr–Zr system were investigated experimentally by using differential scanning calorimetry (DSC), X-ray diffraction (XRD), and Scanning electron microscope (SEM) along with EDX. Arc melting was used to synthesize all of these alloys. The temperature of the Cr and Zr-rich eutectic L ↔ C36–Cr2 Zr + Cr and L ↔ β-Zr + C15–Cr2 Zr were determined to be 1861 ± 3 K and 1588 ± 3 K, respectively. The temperature corresponding to the eutectoid transformation β-Zr ↔ α-Zr + C15–Cr2 Zr was found to be 1099 ± 2 K. The temperature pertaining to C36–Cr2 Zr ↔Cr + C15–Cr2 Zr transformation were determined to be 1844 ± 3 K. These values are notably different from previous measurements and are more accurate. The liquidus temperature in the composition range from 60 to 100 at.% Zr was measured for the first time. All the alloy specimens were characterized by X-ray diffraction. The lattice parameters and relative phase fraction of the constituent phases were evaluated by using Rietveld refinement of the XRD data. At ambient temperature, the refined lattice parameter of C15–Cr2 Zr increases linearly with Zr concentration from 31 (7.199 Å) to 34 at.% Zr (7.210 Å). The oxygen impurities play an important role in the sluggish transformation of the C14/C36–Cr2 Zr ↔ C15–Cr2 Zr Laves phase. The density calculated based on lattice parameters determined by XRD and the theoretical model for anti-site type defects makes it is fair to conclude that C15–Cr2 Zr Laves phase is a substitutional type solid solution. The experimental data presented here is consistent and reliable, and it supersedes previous findings. Highlights: The phase equilibria in the Cr–Zr system were investigated experimentally by using DSC, XRD, and SEM along with EDX. The liquidus temperature in the composition range from 60 to 100 at.% Zr was measured by DSC for the first time. The measured value of Zr-rich eutectic transformation temperature L ↔ C15–Cr2 Zr + β-Zr was found to be 1588 ± 3 K. The equilibrium measured eutectoid transformation temperature β-Zr ↔ α-Zr + C15–Cr2 Zr was found to be 1099 ± 2 K. The lattice parameter of C15–Cr2 Zr increases linearly with Zr concentration from 31 (7.199 Å) to 34 at.% Zr (7.210 Å).